The Financial Effects of Direct Business Subsidies on Finnish Firms : Evidence from Panel Data (2010–2016) - Leivoaro, Juho (My University, 2025)
Finland allocates billions of euros in direct business subsidies annually, yet evidence on their firm-level financial impacts remains limited. Much of the public debate questions whether these subsidies correct genuine market failures or merely redistribute resources without improving economic outcomes. This thesis examines how direct business subsidies affect firms’ leverage and short-run performance using a firm-year panel dataset for 2010–2016. The theoretical framework combines welfare economics and market failure theory with capital structure models. Market failures related to knowledge spillovers, indivisibilities and credit rationing provide an economic rationale for subsidies, while the trade-off and pecking-order theories yield contrasting predictions about how subsidies influence firms’ use of debt. The empirical analysis is based on three datasets: Yle’s direct subsidy data, Orbis balance-sheet data, and a separate scraped dataset containing performance information for smaller firms. The models are estimated using firm and year fixed effects with clustered standard errors. The results show that higher lagged subsidy intensity is associated with significantly higher leverage, suggesting that subsidies ease financing constraints or strengthen balance sheets in a way that enables firms to increase debt financing. However, no short-run effects are found on profitability (ROA) or revenue growth. These findings indicate that while subsidies influence financing decisions, their immediate performance impacts remain modest or may require a longer horizon to materialize. The study contributes to the evaluation of Finnish business subsidies by providing firm-level evidence on how public support interacts with corporate financing behavior.

Suomessa myönnetään vuosittain useita miljardeja euroja yritystukia, mutta niiden vaikutuksista yritysten taloudelliseen käyttäytymiseen on vain vähän systemaattista näyttöä. Julkinen keskustelu on korostanut sekä tukien kohdentumiseen liittyviä ongelmia että epävarmuutta siitä, tuottavatko tuet todellista lisäarvoa. Tutkielman tavoitteena on tutkia, miten suorat yritystuet vaikuttavat yritysten velkaantuneisuuteen sekä lyhyen aikavälin kannattavuuteen ja kasvuun vuosina 2010–2016. Teoreettinen viitekehys yhdistää hyvinvointitaloustieteen ja markkinahäiriöiden teoriat pääomarakenneteorioihin. Innovaatioihin ja luottorajoitteisiin liittyvät markkinapuutteet muodostavat perusteet julkiselle tuelle, kun taas trade-off- ja pecking order -teoriat ennustavat vastakkaisia vaikutuksia siihen, vähentävätkö vai lisäävätkö tuet yritysten velan käyttöä. Empiirinen analyysi perustuu kolmeen aineistoon: Ylen yritystukidataan, Orbis-tilinpäätöstietoihin sekä pienyrityksistä koottuun scraper-aineistoon. Mallit estimoidaan yritys- ja vuosikohtaisilla kiinteillä vaikutuksilla. Tulokset osoittavat, että suurempi tukien intensiteetti edellisenä vuonna on yhteydessä korkeampaan velka-asteeseen. Tämä viittaa siihen, että tuet vahvistavat yritysten rahoitusasemaa tai helpottavat pääsyä velkamarkkinoille. Sen sijaan kannattavuuteen (ROA) ja liikevaihdon kasvuun ei havaita lyhyen aikavälin vaikutuksia. Johtopäätöksenä tuet näyttävät vaikuttavan rahoituspäätöksiin, mutta niiden vaikutukset suorituskykyyn eivät ilmene välittömästi tai voivat vaatia pidemmän tarkastelujakson. Tutkielma tarjoaa empiiristä näyttöä suomalaisen yritystukijärjestelmän toimivuudesta yritystasolla.
Keywords: Suorat Yritystuet, Pääomarakenne, Yrityksen Suorituskyky, Direct Business Subsidies, Capital Structure, Firm Performance